Discourse Analysis on Procedure Text to Practice Self Directing Learning - Hasanah, Qoriatul; Nur Tjendani, Endah; Ghozali, Imam (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2022)
Discourse is language in context referring to language in action, while a text is written record of interaction or communicative event that brings together language, the individual producing the language and context within which language used. So, this research aims to conduct discourse analysis of the student’s difficulties to practice self-directing learning in writing procedure text. The subjects of this research are the total students (25 students) of grade 9 MTS UnggulanNurul Islam Jember with 10 students as the samples of the data. The data collection was conducted by using a random sampling method. The data was categorized according to Donald Aryet all (2010, 8th edition). The approach of this research design was descriptive qualitative that used interactive and humanistic multiple methods to present the data gained from analyzing, observation, literature study, in-depth interviews and documentation study. From the research, it was found that the students did some faulty actions in understanding the description and orders from the teacher especially the language features of procedure text, vocabulary, grammatical and organizational error. Consequently, as the research objectives this eventually will give a positive contribution to the teacher to follow up the difficulties